2020
DOI: 10.1080/0167482x.2020.1713083
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Arabic version of Muller’s prenatal attachment inventory

Abstract: Increased maternal fetal attachment (MFA) is associated to improved health practices. A tool to measure MFA within an Arab cultural context was developed to help health care providers identify and help women with low MFA. Muller's 21-item Prenatal Attachment Inventory (PAI) was translated from English into Arabic and tested on 250 pregnant Arab women in Riyadh, Saudi Arabia to measure its psychometric properties and appropriateness within an Arab cultural context. A cross-sectional quantitative study was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…The European Research Journal 2023 ! nancy had lower prenatal attachment levels than those with healthy pregnancy, there are studies alleging that women with high-risk pregnancy had lower prenatal attachment levels [19,20]. In this current research, the prenatal attachment of women with healthy and highrisk pregnancies was found to be similar and at medium levels.…”
Section: Discussionmentioning
confidence: 40%
See 2 more Smart Citations
“…The European Research Journal 2023 ! nancy had lower prenatal attachment levels than those with healthy pregnancy, there are studies alleging that women with high-risk pregnancy had lower prenatal attachment levels [19,20]. In this current research, the prenatal attachment of women with healthy and highrisk pregnancies was found to be similar and at medium levels.…”
Section: Discussionmentioning
confidence: 40%
“…In this current research, the prenatal attachment of women with healthy and highrisk pregnancies was found to be similar and at medium levels. Likewise, in the relevant literature, pregnant women were in general reported to have 'medium-level' prenatal attachment [10,[19][20][21]. As per Lazarus and Folkman's understanding [22], a prospective mother who is faced with a new situation or change suffers stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, women may internalise rather than externalise their developing bond. Highlighting the importance of cultural appropriateness, Arafah et al (2020) included four new items in the PAI to capture the MFA amongst Arabic-speaking women in Qatar (e.g., 'I am careful with my activities so nothing will hurt my baby'). Future qualitative research might therefore help highlight relevant questions for pregnant women in Pakistan or whether the MFA construct lacks validity in this context.…”
Section: Discussionmentioning
confidence: 99%